MENTAL PROCESSES PERFORM A SIGNAL OR CONTROL FUNCTION AND ADAPT TO THE SITUATION - Guljahon Eshonkulova Abdukhakhorovna (Academia Science Repository, 2023)
Thinking is a generalized reflection of reality, legal connections through words and experience. By determining the laws of development of things and events, man has the opportunity to control the development of nature and human society. Human thinking is closely related to language. Thinking, like all mental processes, is the result of brain activity. It will be discussed about mental processes perform a signal or control function and adapt to the situation.